Relationship of Emotional Intelligence and Academic Performance among Medical Students: Systematic Review - Ivan Rolland Karkada; Urban John Arnold D'Souzaa; Zainal Arifin bin Mustapha (2020)
Introduction: There is a number of research elaborating the role played by the emotional intelligence in educational performance at primary and high school level but seldom among medical students. Objective: The aim of this review paper is to ascertain the relationship between emotional intelligence and academic performance among the medical students. Materials and methods: All articles searched using relevant finalised MeSh (Medical Subject Headings: is the NLM controlled vocabulary thesaurus used for indexing articles for PubMed.) terms are of English language between the years 1980 and 2018 among the following electronic database Ovid - MedLine, ProQuest, Scopus, Science Direct, CINAHL. Articles are further filtered based on the inclusion and exclusion criteria set up by the reviewers with mutual consent. Knowledge about academic output based on the methods involved in measuring emotional intelligence and study design was extracted. Results: The literature review cited 511 relevant articles. These articles are further scrutinised by removing duplicates, considering full text articles, and abstract review availed 07 articles which were considered for final review. It was found that six out of seven showed women had higher EI than men and only one of the seven showed no difference between men and women. Conclusion: In line with literature review, one can safely conclude emotional intelligence (EI), in general, improves academic performance. However, in contrast it is also seen among medical students the EI decreasing over the time of study years. Further research is necessary to find out the cause for this decline in emotional intelligence during the course and whether timely intervention of structured training can improve or not.